2002
DOI: 10.1093/bja/aef173
|View full text |Cite
|
Sign up to set email alerts
|

Propofol attenuates myocardial lipid peroxidation during coronary artery bypass grafting surgery †

Abstract: In clinical doses, propofol strongly attenuates lipid peroxidation during CABG surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
45
0
5

Year Published

2004
2004
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 75 publications
(56 citation statements)
references
References 29 publications
6
45
0
5
Order By: Relevance
“…This effect has also been demonstrated in other human studies using different markers of lipid peroxidation (44).…”
Section: Intravenous Anaestheticssupporting
confidence: 74%
“…This effect has also been demonstrated in other human studies using different markers of lipid peroxidation (44).…”
Section: Intravenous Anaestheticssupporting
confidence: 74%
“…It has also been shown that propofol can attenuate apoptosis in tumor necrosis factor-α-induced endothelial cells and enhance the bioavailability of nitric oxide (Luo et al, 2005). Coronary endothelial cell apoptosis precedes myocyte apoptosis (Sayin et al, 2002). Hence, attenuation of vascular endothelial cell apoptosis by propofol could have resulted in reduced cardiomyocytes apoptosis during myocardial ischemia and reperfusion.…”
Section: Discussionmentioning
confidence: 99%
“…The result showed TBARS level was less signiicantly in propofol group than fentanyl group. (19) The second study included thirty adult patients referred for elective cardiac procedure with Cardio Pulmonary Bypass (CPB) and randomly allocated to a propofol group or a control group. Patients in the propofol group received propofol 0.1 mg/kg/minute intravenously for anesthesia maintenance, whereas those in the control group received fentanyl 10 µg/kg intravenously and inhaled enlurane 1%-1.5%.…”
Section: Effect To Respiratory Systemmentioning
confidence: 99%